Advances in graphene-based optoelectronics, plasmonics and photonics. (8th January 2016) - Nguyen, Bich Ha; Nguyen, Van Hieu
Abstract: Since the early works on graphene it has been remarked that graphene is a marvelous electronic material. Soon after its discovery, graphene was efficiently utilized in the fabrication of optoelectronic, plasmonic and photonic devices, including graphene-based Schottky junction solar cells. The present work is a review of the progress in the experimental research on graphene-based optoelectronics, plasmonics and photonics, with the emphasis on recent advances. The main graphene-based optoelectronic devices presented in this review are photodetectors and modulators. In the area of graphene-based plasmonics, a review of the plasmonic nanostructures enhancing or tuning graphene-light interaction, as well as of graphene plasmons is presented. In the area of graphene-based photonics, we report progress on fabrication of different types of graphene quantum dots as well as functionalized graphene and graphene oxide, the research on the photoluminescence and fluorescence of graphene nanostructures as well as on the energy exchange between graphene and semiconductor quantum dots. In particular, the promising achievements of research on graphene-based Schottky junction solar cells is presented.